Illness beliefs predict mortality in patients with diabetic foot ulcers - Vedhara, Kavita; Dawe, Karen; Miles, Jeremy N.V.; Wetherell, Mark A.; Cullum, Nicky; Dayan, Colin; Drake, Nicola; Price, Patricia; Tarlton, John; Weinman, John; Day, Andrew; Campbell, Rona; et al. (Public Library of Science, 2016)
Abstract Background: Patients’ illness beliefs have been associated with glycaemic control in diabetes and survival in other conditions. Objective: We examined whether illness beliefs independently predicted survival in patients with diabetes and foot ulceration. Methods: Patients (n=169) were recruited between 2002 and 2007. Data on illness beliefs were collected at baseline. Data on survival were extracted on 1st November 2011. Number of days survived reflected the number of days from date of recruitment to 1st November 2011. Results: Cox regressions examined the predictors of time to death and identified ischemia and identity beliefs (beliefs regarding symptoms associated with foot ulceration) as significant predictors of time to death. Conclusions: Our data indicate that illness beliefs have a significant independent effect on survival in patients with diabetes and foot ulceration. These findings suggest that illness beliefs could improve our understanding of mortality risk in this patient group and could also be the basis for future therapeutic interventions to improve survival.